Fibroblasts From Idiopathic Pulmonary Fibrosis Induce Apoptosis and Reduce the Migration Capacity of T Lymphocytes - Chavez-Galan, Leslie; Becerril, Carina; Ruiz, Andy; Ramon-Luing, Lucero A.; Cisneros, José; Montaño, Martha; Salgado, Alfonso; Ramos, Carlos; Buendía-Roldán, Ivette; Pardo, Annie; Selman, Moisés (Frontiers in Immunology, 2022)
Idiopathic pulmonary fibrosis (IPF) is a progressive and irreversible lung disease of unknown etiology. Myofibroblasts are organized in peculiar subepithelial fibroblasts foci (FF), where they abnormally persist and exclude lymphocytes by unclear mechanisms. FF are the source of an excessive extracellular matrix, which results in progressive stiffening and destruction of the lung architecture. We hypothesized that the absence of T cells inside the FF could be related, at least partially, to an inefficient function of lymphocytes induced by IPF fibroblasts. Here, we evaluated the effect of a supernatant from IPF fibroblasts on T-cell apoptosis and migration capacity. Data showed that IPF fibroblasts secrete pro-apoptotic molecules (both from extrinsic and intrinsic pathways), generating a microenvironment that induces apoptosis of T cells at 3 h of culture, despite a weak anti-apoptotic profile exhibited by these T cells. At 24 h of culture, the supernatants from both IPF and control fibroblasts provoked T-cell death. However, at this time of culture, IPF fibroblasts caused a marked decrease in T-cell migration; in contrast, control lung fibroblasts induced an increase of T-cell migration. The reduction of T-cell migratory capacity provoked by IPF fibroblasts was associated with a negative regulation of RHOA and ROCK, two essential GTPases for migration, and was independent of the expression of chemokine receptors. In conclusion, our findings demonstrate that IPF fibroblasts/myofibroblasts induce apoptosis and affect T-cell migration, revealing a mechanism involved in the virtual absence of T lymphocytes inside the FF.